Perception of Malaysian Society Toward Existence of Indonesian Workers in Malaysia - Widyawati, Siska; Muhd Radzi, Sumaiyah Binti (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
The purpose of this research was to find out how the perception of Malaysian society towards Indonesian Workers (TKI) in Malaysia. This research is descriptive intended to describe carefully the particular social phenomena that are being studied by developing concepts and gathering facts by using observation, interview and documentation studies in data collection. The types of data used are primary data and secondary data obtained from Indonesian workers in Malaysia. Primary data is collected by interviewing resource persons and conducting observations or open observations related to the perception of the Malaysian public towards Indonesian migrant workers. The subject of this study is that the Malaysians themselves can provide their views or perceptions of migrant workers, not limited to their social status. The analysis results of this study include: 1) Protection and Legal Status of Indonesian Migrant Workers in Malaysia, 2) The Influence of Indonesian Migrant Workers on availability of employment in Malaysia, 3) Interaction between Indonesian labor migrants and Malaysian society,4) Problems faced by Indonesian labor migrants in Malaysia.